Efficacy of various coated materials to prevent nutrient leaching for Pacific white shrimp Litopenaeus vannamei commercial diets. Issue 1 (25th August 2020) - Guo, Jingping; Davis, Robert; Starkey, Charles; Davis, Donald Allen
Abstract: The physical characteristics and leaching rates of water‐soluble compounds from shrimp feeds are major considerations in nutrient delivery. Yet, there is limited information on nutrient leaching from feeds or the mechanisms to minimize leaching. This study evaluated the efficacy of various coating agents on the physical characteristics and leaching of nutrients from commercial feeds for Litopenaeus vannamei . A series of diets were top coated with two lipid sources (fish or stearin oil) and two additives to the oil (5% wax or gelatin) at three levels (0, 1.5, and 3%). Physical characteristics and leaching of water‐soluble compounds were then characterized. The reduction of leaching was seen with the diets that were top coated with 1.5 or 3% oil, which significantly decreased the leaching of phenylalanine (Phe) after 30 min and 60 min of immersion. Adding 1.5 and 3% oil coating significantly decreased the pellet durability index. Adding gelatin as an additive to the oil significantly slowed sinking velocity and improved water stability and the pellet durability index of the diets. In all, results demonstrated that coating 1.5 or 3% fish or stearin oil decreases the leaching rate. Supplementing 5% gelatin in the coating material for diets can improve the performance of the diets.